Rapamycin interacts synergistically with idarubicin to induce T-leukemia cell apoptosis in vitro and in a mesenchymal stem cell simulated drug-resistant microenvironment via Akt/mammalian target of rapamycin and extracellular signal-related kinase signaling pathways. Issue 3 (March 2014) - Wu, Kang-Ni; Zhao, Yan-Min; He, Ying; Wang, Bin-Sheng; Du, Kai-Li; Fu, Shan; Hu, Kai-Min; Zhang, Li-Fei; Liu, Li-Zhen; Hu, Yong-Xian; Wang, Ying-Jia; Huang, He
Abstract T-cell acute lymphoblastic leukemias (T-ALLs) are clonal lymphoid malignancies with a poor prognosis, and still a lack of effective treatment. Here we examined the interactions between the mammalian target of rapamycin (mTOR) inhibitor rapamycin and idarubicin (IDA) in a series of human T-ALL cell lines Molt-4, Jurkat, CCRF-CEM and CEM/C1. Co-exposure of cells to rapamycin and IDA synergistically induced T-ALL cell growth inhibition and apoptosis mediated by caspase activation via the intrinsic mitochondrial pathway and extrinsic pathway. Combined treatment with rapamycin and IDA down-regulated Bcl-2 and Mcl-1, and inhibited the activation of phosphoinositide 3-kinase (PI3K)/mTOR and extracellular signal-related kinase (ERK). They also played synergistic pro-apoptotic roles in the drug-resistant microenvironment simulated by mesenchymal stem cells (MSCs) as a feeder layer. In addition, MSCs protected T-ALL cells from IDA cytotoxicity by up-regulating ERK phosphorylation, while rapamycin efficiently reversed this protective effect. Taken together, we confirm the synergistic antitumor effects of rapamycin and IDA, and provide an insight into the potential future clinical applications of combined rapamycin–IDA regimens for treating T-cell malignancies.